2004
DOI: 10.1080/1362369042000248802
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS, Peacekeeping and Conflict Crises in Africa

Abstract: This article investigates the impact of the spread of HIV/AIDS on the African military and its ability to act as an effective instrument of conflict resolution in the continent. The capacity of African militaries is particularly important at a time when major powers are reluctant to engage in greater peacekeeping operations in the region. The widespread prevalence of HIV among military personnel threatens political and social stability more generally, and this study focuses on the link between peacekeeping and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…24 These personnel tend to have positions of power and may have higher rates of infection than rates found among the local population. 25 As illustrated by recent reports of sexual abuse by United Nation (UN) peacekeeping forces in the Eastern Democratic Republic of the Congo, the exchange of sex for food further reinforces the link between poverty and abuse, and highlights the unfortunate fact that conflict-related sexual abuse can continue even among peacekeeping efforts.…”
Section: Survival Sex In the Face Of Destroyed Economies And Increasementioning
confidence: 99%
See 1 more Smart Citation
“…24 These personnel tend to have positions of power and may have higher rates of infection than rates found among the local population. 25 As illustrated by recent reports of sexual abuse by United Nation (UN) peacekeeping forces in the Eastern Democratic Republic of the Congo, the exchange of sex for food further reinforces the link between poverty and abuse, and highlights the unfortunate fact that conflict-related sexual abuse can continue even among peacekeeping efforts.…”
Section: Survival Sex In the Face Of Destroyed Economies And Increasementioning
confidence: 99%
“…Similarly, soldiers in locations with a high prevalence rate of HIV/AIDS may spread the disease in their home communities upon return. 24,25 Mass population displacement: refugee movement and internally displaced persons As lawlessness, pervasive violence and socioeconomic conditions worsen with conflict, these conditions cause mass relocation and internal displacement. As fleeing populations move to areas of temporary safety, refuge is sought in makeshift settlements or camps.…”
Section: High Incidence Of Hiv Infection Among Armed Combatantsmentioning
confidence: 99%
“…HIV, the human immunodeficiency virus, can pose a significant threat to a country's stability and security, particularly when the country's military has high rates of infection (Altman 2003;Heinecken 2001;Tripodi and Patel 2004;Yeager and Kingma 2001). Soldiers, many of whom are young sexually active men, are at great risk of acquiring and spreading HIV.…”
Section: Introductionmentioning
confidence: 98%
“…Many reports have shown that teenagers, young adults and military personnel are mostly infected 3,6,7 . In most African countries, the HIV infection amongst the military has been shown to be about 2 to 5 times higher than their civilian counterparts 8,9,10,11 . Several factors have been implicated in the increased vulnerability of the personnel in military service to HIV infection; these include being mobile and away from home, less subject to social controls, subject to professional ethos that tends to excuse or encourage risk-taking, young and sexually active, inclined to risk behavior including risky sex and substance abuse, deployed where alcohol 12 , drugs and prostitution may be easily accessible or available and, often in a position where they have more money, more power and more influence than the local population 10,13,14 .…”
Section: Introductionmentioning
confidence: 99%